FAKTOR-FAKTOR YANG MEMPENGARUHI LITERASI SAINS SISWA INDONESIA BERUSIA 15 TAHUN - HARIADI, EKO (Pendidikan Dasar, 2009)
Abstract: Main purpose of this research was to indentify factors influencing science literacy of 15-years-olds students. The subjects of the research were 5330 students enrolled in SMP, 926 students in MTs, 2638 students in SMA, 240 students in MA, and 1513 students in SMK. The main focus of PISA 2006 was science. The PISA 2006 survey also sought information on students’ attitudes to science. Each participating student spent two hours carrying out pencil-and-paper tasks. Students also answered a questionnaire that took about 30 minutes to complete and focused on their personal background, their learning habits and their attitudes to science, as well as on their engagement and motivation. There were 15 indicators extracted from the questionnaire and 5 plausible scores from PISA science assessment. Students’ responses from the questionnaire and assessment were tested using Structural Equation Modeling. Variables latent confirmed were students’ background, students’ attitudes to science, learning/teaching strategies, useful for science career, time for learning science, and science performance. Students’ science literacy is influenced by students’ attitudes to science and their background. Science literacy correlated negatively with  problem based learning, using phenomena to illustrate science topics, and lab enquiry. However, science literacy correlated positively with peer teaching and modeling strategies.